Building capacity - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Building capacity Writing from PO Box 2275, Bungoma, Kenya, Dr E J Mukhwana, Director of the Sustainable Agriculture Centre for Research and Development in Africa (SACRED), shares his organisation's experience in capacity building: 'SACRED has been...